Anti–SARS-CoV-2 antibodies in the CSF, blood-brain barrier dysfunction, and neurological outcome: Studies in 8 stuporous and comatose patients. Issue 6 (November 2020) - Alexopoulos, Harry; Magira, Eleni; Bitzogli, Kleopatra; Kafasi, Nikolitsa; Vlachoyiannopoulos, Panayiotis; Tzioufas, Athanasios; Kotanidou, Anastasia; Dalakas, Marinos C.
Abstract : Objective: To investigate the pathophysiologic mechanism of encephalopathy and prolonged comatose or stuporous state in severally ill patients with coronavirus disease 2019 (COVID-19). Methods: Eight COVID-19 patients with signs of encephalopathy were tested for antibodies to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the serum and CSF using a Food and Drug Administration-approved and independently validated ELISA. Blood-brain barrier (BBB) integrity and immunoglobulin G (IgG) intrathecal synthesis were further tested using albumin and IgG indices. The CSF was also tested for autoimmune encephalitis antibodies and 14-3-3, a marker of ongoing neurodegeneration. Results: All patients had anti–SARS-CoV-2 antibodies in their CSF, and 4 of 8 patients had high titers, comparable to high serum values. One patient had anti–SARS-CoV-2 IgG intrathecal synthesis, and 3 others had disruption of the blood-brain barrier. The CSF in 4 patients was positive for 14-3-3-protein suggesting ongoing neurodegeneration. In all patients, the CSF was negative for autoimmune encephalitis antibodies and SARS-CoV-2 by PCR. None of the patients, apart from persistent encephalopathic signs, had any focal neurologic signs or history or specific neurologic disease. Conclusions: High-titer anti-SARS-CoV-2 antibodies were detected in the CSF of comatose or encephalopathic patients demonstrating intrathecal IgG synthesis or BBB disruption. A disrupted BBB may facilitate the entry of cytokines and inflammatory mediators into the CNS enhancing neuroinflammation and neurodegeneration. The observations highlight the need for prospective CSF studies to determine the pathogenic role of anti–SARS-CoV-2 antibodies and identify early therapeutic interventions.